PENERAPAN METODE INQUIRY PADA MATA PELAJARAN PENDIDIKAN AGAMA BUDDHA MATERI BIJA NIYAMA DI SMA NEGERI 1 GIRIMULYO - Via Estiana; Dwi Maryani Rispatiningsih; Dwiyono Putranto (Jurnal Muara Pendidikan, 2022)
This study aims to describe the process of optimizing the preparation using the inquiry learning model at SMA Negeri 1 Girimulyo, the learning process using the inquiry learning model, and the process of evaluating the application of the inquiry learning model to the Bija niyama material. This study uses descriptive qualitative research methods. The subjects of this study were students in class X at SMA Negeri 1 Girimulyo. Data collection was carried out by interview, observation, and documentation. The validity of the data in this study used triangulation. The results of the study show that the preparation for the application of the inquiry learning model to Buddhist education subjects for class X students was carried out by researchers by preparing lesson plans, preparing learning objectives, learning methods, learning materials, and learning media. Through maximum preparation of learning activities, the application of the guided inquiry learning model can increase student activity while learning. Student responses during learning are good and enthusiastic so that students can understand the subject matter well. For this reason, the application of the inquiry learning model to the Bija Niyama material has been successfully implemented.